Petrogenesis of Andesite in Cisanggarung area, Cimenyan District, Bandung Regency, West Java - Imaniar, Nurul; Patonah, Aton; Prambada, Oktory (Fakultas Teknik Geologi Universitas Padjadjaran, 2021)
The Cisanggarung area is located in Cimenyan District, Bandung Regency, an area composed of volcanic products that many thick outcrops are found and used as andesite mines managed by local communities. This study examines the characteristics of andesite in the Cisanggarung area using petrology, petrography, XRF, and ICP-MS so that petrogenesis can be interpreted. Andesite rocks in the Cisanggarung area have a sheeting joint structure and microscopically have porphyritic, trachytic, glomeroporphyritic, zoning, embayment, and sieve textures. The composition of this rock was plagioclase, pyroxenes, opaque minerals with the less content of secondary minerals such as chlorite and clay minerals. The magmatic affinity of this rock shows calc-alkaline series, precisely in tholeiitic island arc tectonic setting associated with subduction, which is characterized by TiO2<1.3 wt.%. Magma presumably comes from a continent plate with a depth of 127.87-136.92 km. Magma in this area undergoes a middle-stage differentiation process, namely assimilation and fractionation crystallization. The magmatism process forms two stages of crystallization, starting from the slow cooling stage, followed by relatively fast magma to the surface.